An ecosystem approach to teacher professional development within computer science. Issue 4 (2nd October 2018) - Falkner, Katrina; Vivian, Rebecca; Williams, Sally-Ann
ABSTRACT: Computer Science (CS) curricula are being adopted worldwide. However, the lack of prior teaching training within this area means that we have an urgent need to provide teacher professional development. Best practice teacher professional development motivates us to construct interactive and sustainable models of professional development. However, there are challenges in doing this at the scale that we need and with the resources that are available. In this paper, we describe an ecosystem-based approach to supporting teacher professional development, aligned with best practices and with teachers' and schools' needs. An ecosystem approach operates under the coordination of a governance model, features a central hub and conceptualises the relationships of the organisations as a network. Ecosystems are underpinned by value co-creation, shared logic and can be non-geographical. We believe an ecosystem view of a teacher professional development program supports sustainability, authenticity and flexibility in how teachers engage with professional development, positioning teachers as co-contributors.